Analysis of Project-Based Learning in IPAS Subjects at Madrasah Ibtidaiyah: A Progressivism Perspective - Sari, Putri Sekar; Maemonah, Maemonah (Departemen Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari Banjarmasin, 2024)
Education is one of the most essential parts of advancing a nation. To realize quality education, it is necessary to have guidelines for planning and implementing quality learning. This study aims to analyze the extent to which the implementation of project-based learning in IPAS (Integrated Natural and Social Sciences) subjects in Madrasah Ibtidaiyah aligns with the philosophical principles of progressivism. This research adopts a qualitative approach grounded in progressivist philosophy. The methodology employed is library research, drawing on data from various sources, including books and research articles published in the last decade (2015-2024), conference proceedings, and other materials pertinent to the research topic. Upon collecting all relevant data, the analysis was conducted systematically, involving data reduction, data display, and the drawing of conclusions. The study's findings indicate that the application of project-based learning in IPAS subjects is consistent with the principles of progressivism. Specifically, this approach promotes student-centred learning with teachers as facilitators, guides, and mentors. It encourages active student participation and fosters a collaborative learning environment where everyone is engaged and part of the educational process, focusing on material comprehension and problem-solving. The implications of this research suggest that it could enhance the quality of education by fostering more innovative and creative learning experiences. However, the study does acknowledge certain limitations, particularly concerning the range of research sources utilized and the implementation of the research. Therefore, it is recommended that future researchers expand upon this work by incorporating field research methodologies.